Hesitant triangular fuzzy generalized geometric heronian mean in MCDM - Wan Abdul Rahman, Wan Syaidatul Izzati; Md Rodzi, Zahari (Universiti Teknologi MARA, Perak, 2025)
This paper introduces a new aggregator, the Hesitant Triangular Fuzzy Generalized Geometric Heronian Mean (HTFGGHM). The hesitant triangular fuzzy set (HTFS) combined with the Generalized Geometric Heronian mean (GGHM), makes the HTFGGHM operator capable of ensuring reasonable aggregation through desirable indexes such as idempotency, monotonicity, and boundedness. As will be shown, it manages to retain the inherent uncertainty and correlation of the criteria while offering clear and coherent rankings. Incorporating the carefulness of hesitant fuzzy sets and the compute-intensive power of GGHM, the HTFGGHM operator improves the decision accuracy and hence serves as a handy tool to tackle vague situations in a multi-attribute decision-making process.